Assessing the values-based context of conservation for modern architectural heritage: a study on the Headquarters Building of the TR 17th Regional Directorate of Highways Complex, Istanbul - Durusoy Ozmen, Elifnaz; Omay Polat, Ebru (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2021)
This article contributes to the debate on modern architectural heritage by emphasizing the values-based context of conservation. Considering the abstractness of the concepts and the clarity of realities, the paper tries to introduce the uncertainty of the valuation phase for the conservation of modern architectural heritage by presenting a remarkable case study: The Headquarters Building of the Turkish Republic (T.R.) 17th Regional Directorate of Highways Complex, Istanbul. Designed by Mehmet Konuralp in 1973, the Headquarters, as one of the first skyscrapers in Istanbul presenting the basic qualities of modernism, was listed as an architectural asset in 2004 based on its art-design, artistic-technical, social, and symbolic values. However, it fell victim to a series of decisions taken by administrative authorities on the grounds that the attributed values are not worth protecting. Through a comprehensive analysis of the Headquarters, this study intends to demonstrate the incomplete understandings of modern architectural heritage and its values, as well as to present a discussion concerning similar cases at risk. As a concluding remark, the existing values-based approach of conservation for the modern architectural heritage calls into question and some initial possibilities are proposed to raise awareness.
Keywords: Values; conservation; modern architectural heritage; the Headquarters Building of the T; R; 17th Regional Directorate of Highways Complex; Istanbul; Architecture